Magnetosphere‐Ionosphere‐Thermosphere Coupling Study at Jupiter Based on Juno's First 30 Orbits and Modeling Tools. Issue 10 (9th October 2022) - Al Saati, S.; Clément, N.; Louis, C.; Blanc, M.; Wang, Y.; André, N.; Lamy, L.; Bonfond, B.; Collet, B.; Allegrini, F.; Bolton, S.; Clark, G.; et al.
Abstract: The dynamics of the Jovian magnetosphere is controlled by the interplay of the planet's fast rotation, its solar‐wind interaction and its main plasma source at the Io torus, mediated by coupling processes involving its magnetosphere, ionosphere, and thermosphere. At the ionospheric level, these processes can be characterized by a set of parameters including conductances, field‐aligned currents, horizontal currents, electric fields, transport of charged particles along field lines including the fluxes of electrons precipitating into the upper atmosphere which trigger auroral emissions, and the particle and Joule heating power dissipation rates into the upper atmosphere. Determination of these key parameters makes it possible to estimate the net transfer of momentum and energy between Jovian upper atmosphere and equatorial magnetosphere. A method based on a combined use of Juno multi‐instrument data and three modeling tools was developed by Wang et al. (2021, https://doi.org/10.1029/2021ja029469 ) and applied to an analysis of the first nine orbits to retrieve these parameters along Juno's magnetic footprint. We extend this method to the first 30 Juno science orbits and to both hemispheres. Our results reveal a large variability of these parameters from orbit to orbit and between the two hemispheres. They also show dominant trends. Southern current systems are consistent with the generation of a region of sub‐corotating ionospheric plasma flows, while both super‐corotating and sub‐corotating plasma flows are found in the north. These results are discussed in light of the previous space and ground‐based observations and currently available models of plasma convection and current systems, and their implications are assessed. Key Points: We analyze the first 30 orbits of Juno to retrieve the properties of current systems and plasma flows associated with Jovian main auroras Southern hemisphere results are consistent with ionospheric plasma sub‐corotation The two opposite patterns, sub‐corotation and super‐corotation, are observed in the northern hemisphere